Profound Change in Soil Microbial Assembly Process and Co-occurrence Pattern in Co-inoculation of Bradyrhizobium japonicum 5038 and Bacillus aryabhattai MB35-5 on Soybean - Zhao, Yubin; Guan, Dawei; Liu, Xu; Gao, Gui-Feng; Meng, Fangang; Liu, Bingqiang; Xing, Pengfei; Jiang, Xin; Ma, Mingchao; Cao, Fengming; Li, Li; Li, Jun (Frontiers in Microbiology, 2022)
Rhizosphere microbial communities are vital for plant growth and soil sustainability; however, the composition of rhizobacterial communities, especially the assembly process and co-occurrence pattern among microbiota after the inoculation of some beneficial bacteria, remains considerably unclear. In this study, we investigated the structure of rhizomicrobial communities, their assembly process, and interactions contrasting when Bradyrhizobium japonicum 5038 and Bacillus aryabhattai MB35-5 are co-inoculated or Bradyrhizobium japonicum 5038 mono-inoculated in black and cinnamon soils of soybean fields. The obtained results indicated that the Chao and Shannon indices were all higher in cinnamon soil than that in black soil. In black soil, the co-inoculation increased the Shannon indices of bacteria comparing with that of the mono-inoculation. In cinnamon soil, the co-inoculation decreased the Chao indices of fungi comparing with that of mono-inoculation. Compared with the mono-inoculation, the interactions of microorganisms of co-inoculation in the co-occurrence pattern increased in complexity, and the nodes and edges of co-inoculation increased by 10.94%, 40.18% and 4.82%, 16.91% for bacteria and fungi, respectively. The co-inoculation of Bradyrhizobium japonicum 5038 and Bacillus aryabhattai MB35-5 increased the contribution of stochastic processes comparing with Bradyrhizobium japonicum 5038 inoculation in the assembly process of soil microorganisms, and owing to the limitation of species diffusion might restrict the direction of pathogenic microorganism movement. These findings support the feasibility of rebuilding the rhizosphere microbial system via specific microbial strain inoculation and provide evidence that the co-inoculation of Bradyrhizobium japonicum 5038 and Bacillus aryabhattai MB35-5 can be adopted as an excellent compound rhizobia agent resource for the sustainable development of agriculture.